2022
DOI: 10.3389/fmicb.2022.975271
|View full text |Cite
|
Sign up to set email alerts
|

Microbial community structure and shift pattern of industry brine after a long-term static storage in closed tank

Abstract: Brine from Dingyuan Salt Mine (Anhui, China), an athalassohaline hypersaline environment formed in the early tertiary Oligocene, is used to produce table salt for hundreds of millions of people. However, halophiles preserved in this niche during deposition are still unknown. Here, we employed cultivation and high-throughput sequencing strategies to uncover the microbial community and its shift after a long-term storage in the brine collected from Dingyuan Salt Mine. High-throughput sequencing showed (1) in the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 72 publications
0
1
0
Order By: Relevance
“…The Geothermobacter genus, iron-reducing bacterium (Gomez-Saez et al, 2017), and the Desulfovermiculus, sulfate-reducing bacterium (Nigro et al, 2020) are usually found in hypersaline environments where they play a key role in iron and sulfur cycling. The archaeal phylum Halobacteriota was dominated by Halapricum (6.1%), Halorubrum (3.6%), and Natronomonas (2.2%) genera (representing, respectively, 12, 7, and 4.3% of the phylum), isolated in hypersaline ecosystems where they often represent the dominant archaeal taxa (Tu et al, 2022). Halorubrum and Natronomonas are known as aerobes (Mora-Ruiz et al, 2018), while Halapricum is a sulfate-reducing archaeon (Sorokin et al, 2022).…”
Section: Discussionmentioning
confidence: 99%
“…The Geothermobacter genus, iron-reducing bacterium (Gomez-Saez et al, 2017), and the Desulfovermiculus, sulfate-reducing bacterium (Nigro et al, 2020) are usually found in hypersaline environments where they play a key role in iron and sulfur cycling. The archaeal phylum Halobacteriota was dominated by Halapricum (6.1%), Halorubrum (3.6%), and Natronomonas (2.2%) genera (representing, respectively, 12, 7, and 4.3% of the phylum), isolated in hypersaline ecosystems where they often represent the dominant archaeal taxa (Tu et al, 2022). Halorubrum and Natronomonas are known as aerobes (Mora-Ruiz et al, 2018), while Halapricum is a sulfate-reducing archaeon (Sorokin et al, 2022).…”
Section: Discussionmentioning
confidence: 99%